“There was little work to do…”: Ivan Goncharov as a translator at the Foreign Trade Department - Alexandra Romanova (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
From 1835 to 1856, Ivan Goncharov served at the Foreign Trade Department of the Russian Empire Ministry of Finance. From 1838 to 1851, Goncharov’s work in the 2nd department of the Department consisted of translating foreign documents into Russian. In the early 1990s a staff member of the Goncharov Museum (Ulyanovsk) A.V. Lobkareva discovered Goncharov's translation — a note from the Prussian government (1845). Until now, this finding remains the only known Goncharov's translation. The article substantiates the reason why the researchers could not find other translations. Books and articles providing the information about the nature of Goncharov’s service are analyzed. The list and biographical data of the translators who served at the same time are given. In the course of research, the file of G.F. Litvinov, Goncharov’s colleague, was discovered in the Russian State Historical Archive. Litvinov translated the encrypted letters of smugglers from the western borders written in “Hebrew” language (that is, in Yiddish). In his appeal to the authorities Litvinov described his work, giving indirect information to assess the volume and complexity of his colleagues’ work. An overview of files reviewed by the author of the article is given. The data on the write-off of unnecessary documentation from the archives of the department in the 1830s, 1840s, 1860s is presented. The hypothesis is formulated that the translation of foreign-language petitions, applications, etc., was carried out at the first appeal; the finished translation was then used and anonymously included in petitions, “notes” and other documents. It has been suggested that the preservation of the original text and translation was not considered necessary, since official documentation was conducted only in the state language.